Determination the Optimal Conditions of Methylene Blue Adsorption by the Chicken Egg Shell Membrane - Salman, Dhuha D.; Ulaiwi, Wisam S.; Tariq , N.M. (International Journal of Poultry Science, 2012)
The use of natural, cheaper and effective adsorbents like egg shell and its membrane and their mixture to bind three different types of dyes, methylene blue (cation), bromophenol blue (anion) and methyl orange (anion) from their aqueous solutions were investigated. The results indicate that the chicken Egg Shell Membrane (ESM) has the greater affinity for methylene blue than the other dyes. The egg shell membrane had a larger capacity to adsorb methylene blue (about 1.35 to 1.65 fold) as compared with Egg Shell (ES) and the mixture of Egg Shell and Membrane (ES+M). The optimum conditions for methylene blue adsorption including, particle size of the adsorbent (75, 125, 150, 212, 250 μm), pH (2, 4, 6, 8, 10), temperature (20, 40, 60, 80, 100)°C, contact time (5, 10, 15, 30, 60 min), adsorbent concentration (0.125, 0.25, 0.5, 0.75, 1.0 g/100 ml) and dye concentration (2, 4, 6, 8, 10 mg/100 ml) were investigated. The results showed that the highly percentages of dye removal by using egg shell membrane were observed with particle size of 250 μm, pH 10, at 80°C, for 30 min with 1.0 g/100 ml adsorbent and 2 mg/100 ml dye concentration.